Durian Village Development Strategy as an Alternative to Increasing the Economy of the Community of Wonosalam Village, Jombang Regency - Risqi Firdaus Setiawan; Hamidah Hendrarini; Heri Susanto (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
In Wonosalam Village, Jombang Regency, Kampung durian possesses various natural and human resources that can serve as the foundation for local economic growth. This study seeks to assess the potential and business development strategy for durian in Wonosalam Village, Jombang Province. Internal and external analysis using the IFAS and EFAS matrices yielded a total score of 2,729 for strengths, 0.49 for weaknesses, 2.23 for opportunities, and 0.63 for threats. This demonstrates that the strength and opportunity factors greatly impact the Wonosalam Durian village's development. Moreover, the SWOT matrix analysis yielded the highest results in the strategy, namely Strength and Opportunity; therefore, in the development of Wonosalam durian village, it is possible to implement a strategy that focuses on enhancing quality and expanding durian product offerings.